2022
DOI: 10.1542/peds.2022-056492
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19–Associated Croup in Children

Abstract: Introduction As SARS-CoV-2 has evolved, so has its effects on the pediatric population.1 While early variants typically resulted in lower respiratory infections, the recently identified Omicron variant may exhibit a predilection for the upper airways.2 The relatively smaller upper respiratory tract in children compared to adults has been thought to predispose them to more severe clinical presentations resembling laryngotracheobronchitis, or croup. Caused by viral-induced subglottic airway inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
77
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(91 citation statements)
references
References 9 publications
(8 reference statements)
11
77
1
2
Order By: Relevance
“…A similar surge was seen by colleagues on the other side of the country, confirming this observation is more than just local to our practice. 13 This increase was not temporally associated with the circulation of parainfluenza virus, and indeed Omicron replaced parainfluenza as the predominant virus associated with croup during this time. Viral testing is not routinely recommended for patients with croup; testing that was performed was for a wide variety of patients and indications, but we do believe our data is a reasonable proxy for local population prevalence.…”
Section: Discussionmentioning
confidence: 92%
“…A similar surge was seen by colleagues on the other side of the country, confirming this observation is more than just local to our practice. 13 This increase was not temporally associated with the circulation of parainfluenza virus, and indeed Omicron replaced parainfluenza as the predominant virus associated with croup during this time. Viral testing is not routinely recommended for patients with croup; testing that was performed was for a wide variety of patients and indications, but we do believe our data is a reasonable proxy for local population prevalence.…”
Section: Discussionmentioning
confidence: 92%
“…Two recent studies conducted in Seattle Children’s Hospital and Boston Children’s Hospital observed a marked increase in cases of croup during the omicron surge. 3 10 Tests for COVID-19 were more likely to be positive in children with croup during the omicron wave compared to those during the delta wave. Similarly, our study observed a sudden increase in the proportion of children with COVID-19 hospitalized due to moderate to severe croup in February 2022, when the omicron variant became dominant in South Korea.…”
mentioning
confidence: 93%
“…2 Sporadic case reports suggest severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) as a pathogen responsible for croup, and many clinicians have observed spikes in croup cases during the current omicron (B.1.1.529) wave. 3 4 5 6 7 8 9 10 Herein, we report a recent sharp rise in pediatric coronavirus disease 2019 (COVID-19) cases requiring hospitalization due to croup during the omicron surge in Seoul, South Korea.…”
mentioning
confidence: 99%
See 2 more Smart Citations